Pendidikan Inklusif di Indonesia: Peluang dan Tantangan - Biantoro, Oktio Frenki; Rahmatullah, Asep (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
Inclusive education in Indonesia in recent years has received appreciation from several researchers. Inclusive education itself is actually not something that is